2020
DOI: 10.21203/rs.2.20529/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between Dietary Energy Density and Mental Health in Overweight/Obese Women

Abstract: Objectives: Mental health, sleep quality and dietary intake are interlinked. Impairment of mental health and low sleep quality may contribute to obesity through the consumption of diets high in energy density. Nevertheless, it is not clear whether dietary energy density (DED) influences mental health. This study aimed to examine the association of DED with mental health indices, including depression, anxiety, stress, and sleep quality in overweight/obese women.Results: After adjustment for age, BMI, and physic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…Respondents who sleep more per night would have a higher BMI as well. This output is supported by previous studies (Maddahi et al, 2020;Salarzadeh Jenatabadi et al, 2020).…”
Section: Discussion Based On Taguchi Methodssupporting
confidence: 88%
“…Respondents who sleep more per night would have a higher BMI as well. This output is supported by previous studies (Maddahi et al, 2020;Salarzadeh Jenatabadi et al, 2020).…”
Section: Discussion Based On Taguchi Methodssupporting
confidence: 88%
“…As the results of the present study revealed, stress was one of the factors affecting tooth decay. The results of various studies (33,(76)(77)(78)(79)(80) indicate this finding and Panagiotou et al (35), no relationship was observed between stress and tooth decay in children. In justifying this discrepancy, we can point to possible differences in the rate of tooth decay and stress, as well as differences in stress measuring tools and indices used in these two studies compared to the present study.…”
Section: Discussionmentioning
confidence: 86%
“…It will affect the immune system by [1] compromising host resistance to cariogenic bacteria ( 27 ) reducing salivary secretion which will to decreased clearance ( 28 , 29 ), [2] unhealthy emotional eating habits followed by frequent snacking and more intake of sugar contained diet ( 30 , 31 ) and finally [3] impaired implementation of self-care habits ( 32 ). Noradrenaline and corticotropin-releasing hormone will also reduce appetite in times of stress; while cortisol is known as an appetite stimulant during stress relief ( 33 ). In fact, extensive and complex internal and external factors will affect appetite and consequently, the amount and the type of food consumed by humans.…”
Section: Introductionmentioning
confidence: 99%